Trustworthy global computing : 10th International Symposium, TGC 2015 Madrid, Spain, August 31-September 1, 2015, Revised selected papers /: 10th International Symposium, TGC 2015 Madrid, Spain, August 31-September 1, 2015, Revised selected papers. (2016) - Unknown
No abstract available